Is There a Link between Mitochondrial Reserve Respiratory Capacity and Aging? - Claus Desler; Thomas Lau Hansen; Jane Bruun Frederiksen; Maiken Lise Marcker; Keshav K. Singh; Lene Juel Rasmussen (Journal of Aging Research)
Oxidative phosphorylation is an indispensable resource of ATP in tissues with high requirement of energy. If the ATP demand is not met, studies suggest that this will lead to senescence and cell death in the affected tissue. The term reserve respiratory capacity or spare respiratory capacity is used to describe the amount of extra ATP that can be produced by oxidative phosphorylation in case of a sudden increase in energy demand. Depletion of the reserve respiratory capacity has been related to a range of pathologies affecting high energy requiring tissues. During aging of an organism, and as a result of mitochondrial dysfunctions, the efficiency of oxidative phosphorylation declines. Based on examples from the energy requiring tissues such as brain, heart, and skeletal muscle, we propose that the age-related decline of oxidative phosphorylation decreases the reserve respiratory capacity of the affected tissue, sensitizes the cells to surges in ATP demand, and increases the risk of resulting pathologies.